The study of sustainable tourism development in Thailand from stakeholder's perceptions: A case study of Amphawa - Chaosukhum, Potjana (2008)
This paper examines the important factors for sustainable tourism development in Thailand by implementing Amphawa as a case study. The primary and secondary data are used to explore the perception of stakeholders that are Thai government, local authority, local business owner, local people and tourist. The interviews of twenty three participants as the representatives of stakeholders were conducted in the area for primary data. From the study, perceptions of stakeholders are relatively the same in most topics. However, tourist is only one group of stakeholder that does not agree with the situation of sustainable tourism development in the area recently. The comparison of the perceptions of the different groups and the analysis of the responses gives insights on the successful implementation of sustainable tourism development. Moreover, this paper analyses the essential factors for sustainable tourism development in Thailand as a whole such as support from the government and community participation. Stakeholders mentioned that the government should provide more education for host community and tourists to conduct tourism in sustainable way. Even though Thailand already has numbers of plan for sustainable tourism development, the most important thing is not only the correct implementation and practicality of them but the incorporation of all participants perceptions and views which can contribute to the success of the plans in the long future.